Design and Verification of a Novel Perfusion Bioreactor to Evaluate the Performance of a Self-Expanding Stent for Peripheral Artery Applications - Nandan, Swati; Schiavi-Tritz, Jessica; Hellmuth, Rudolf; Dunlop, Craig; Vaughan, Ted J.; Dolan, Eimear B. (Frontiers in Medical Technology, 2022)
Endovascular stenting presents a promising approach to treat peripheral artery stenosis. However, a significant proportion of patients require secondary interventions due to complications such as in-stent restenosis and late stent thrombosis. Clinical failure of stents is not only attributed to patient factors but also on endothelial cell (EC) injury response, stent deployment techniques and stent design. Three-dimensional in vitro bioreactor systems provide a valuable testbed for endovascular device assessment in a controlled environment replicating haemodynamic flow conditions found in vivo. To date, very few studies have verified the design of bioreactors based on applied flow conditions and its impact on wall shear stress, which plays key role in development of vascular pathologies. In this study, we develop a computationally informed bioreactor capable of capturing responses of Human Umbilical Vein Endothelial Cells (HUVECs) seeded on silicone tubes subjected to haemodynamic flow conditions and deployment of a self-expanding nitinol stents. Verification of bioreactor design through computational fluid dynamics (CFD) analysis confirmed the application of pulsatile flow with minimum oscillations. EC responses based on morphology, nitric oxide (NO) release, metabolic activity, and cell count at day 1 and day 4 verified presence of haemodynamic flow conditions. For the first time, it is also demonstrated that the designed bioreactor is capable of capturing EC responses to stent deployment beyond a 24-hour period with this testbed. A temporal investigation of EC responses to stent implantation from day 1 to day 4 showed significantly lower metabolic activity, EC proliferation, no significant changes to NO levels and EC’s aligning locally to edges of stent struts and random orientation in between the struts. These EC responses were indicative of stent induced disturbances to local haemodynamics and sustained EC injury response contributing to neointimal growth and development of in-stent restenosis. This study presents a novel computationally informed 3D in vitro testbed to evaluate stent performance in presence of haemodynamic flow conditions found in native peripheral arteries and could help to bridge the gap between the current capabilities of 2D in vitro cell culture models and expensive pre-clinical in vivo models.